Comparison of short-term effects of mobilization with movement and Kinesiotaping on pain, function and balance in patellofemoral pain - Serdar Demirci; Gizem Irem Kinikli; Michael J. Callaghan; Volga Bayrakci Tunay (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: The aim of this study was to compare the short-term effects of Mobilization with movement (MWM) and Kinesiotaping (KT) on patients with patellofemoral pain (PFP) respect to pain, function and balance. Methods: Thirty-five female patients diagnosed with unilateral PFP were assigned into 2 groups. The first group (n = 18) received two techniques of MWM intervention (Straight Leg-Raise with Traction and Tibial Gliding) while KT was applied to the other group (n = 17). Both groups received 4 sessions of treatment twice a week for a period of 2 weeks with a 6-week-home exercise program. Pain severity, knee range of motion, hamstring flexibility, and physical performance (10-step stair climbing test, timed up and go test), Kujala Patellofemoral Pain Scoring and Y-Balance test were assessed. These outcomes were evaluated before the treatment, 45 min after the initial treatment, at the end of the 4-session-treatment during 2-week period and 6 weeks later in both groups. Results: Both treatment groups had statistically significant improvements on pain, function and balance (p < 0.05). Pain at rest (p = 0.008) and the hamstring muscle flexibility (p = 0.027) were demonstrated significant improvements in favor of MWM group. Conclusions: Our results demonstrated similar results for both treatment techniques in terms of pain, function and balance. The MWM technique with exercise had a short-term favorable effect on pain at rest and hamstring muscle flexibility than the KT technique with exercise in patients with PFP. Level of evidence: Level I, therapeutic study. Keywords: Patellofemoral pain, Manual therapy, Mulligan's mobilization, Taping